The Incidence and Predictors of Thromboembolic Events in Patients with Lung Cancer - Bohdan Kadlec (The Scientific World Journal, 2014)
Patients with lung cancer experience elevated risk of venous thromboembolism. Cancer patients with thrombosis have a shorter life expectancy and the occurrence of VTE worsens the quality of life and may delay, interrupt, or completely halt the cancer therapy. In a large cohort of lung cancer patients we monitored the incidence of venous thromboembolism and we identified groups of patients with the highest risk of venous thromboembolism suitable for antithrombotic prophylaxis, which could favourably affect their morbidity and mortality.